Three new species of Zaischnopsis Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae) from Southern China, with redescription of Zaischnopsis tubatius (Walker) - Peng, Lingfei; Xiang, Jiawei; Liu, Qifei (Zootaxa, 2018)
Three new species of Zaischnopsis Ashmead from southern China, Z. candetibia Peng sp. nov., Z. fumosa Peng & Xiang sp. nov. and Z. nivalinota Peng & Xiang sp. nov., are described and illustrated based on females. The only other species of Zaischnopsis recorded from China, Z. tubatius (Walker) is redescribed and illustrated in detail, and the species are differentiated in a key that includes all Zaischnopsis species recorded from the Oriental region.